PENGARUH SUHU PENGERINGAN TERHADAP MUTU ROSELLA KERING (Hibiscus sabdariffa) - Rita Hayati (Jurnal Floratek, 2011)
The objective of the research was to study effects of drying temperatures (sun drying, 50°C, and 60°C) on quality of dried rosella. Moisture content analysis showed that there were not significantly different among all treatments. However, antocianin and vitamin C content were significantly different in all treatments, and the best drying temperature was 50°C. The brightest color of dried rosella was produced by sun drying.  However, all treatments were browning due to Millard reaction.